Does carbon mitigation depend on green fiscal policy or green investment?. (1st April 2023) - Hu, Yufeng; Ding, Youqiang; Liu, Jun; Zhang, Quanzhong; Pan, Zijian
Abstract: Does carbon mitigation depend on the force of government or the autonomy of enterprises? We should first distinguish the roles of green fiscal policy and corporate green investment to test whether they can independently guide enterprises to reduce carbon emissions. Because a clear relationship will help resolve the embarrassment caused by their different goals. Then we use theoretical and empirical methods to analyze green fiscal policies and corporate green investment mechanisms, which have nonlinear impacts on carbon mitigation in mathematics. Furthermore, we have empirically verified then in three effective paths: the promotion of green fiscal policies on green investment, the mediator of green investment in the influence of green fiscal policies on carbon mitigation and enterprise performance, and the difference in firm heterogeneity on green investment. The results show that green fiscal policies support enterprises in realizing carbon mitigation by pressure, stimulating green investment, and achieving Innovation Compensation . Carbon mitigation depends on the trigger of green fiscal policies and the catalysis of green investment. That means the green fiscal policy is an effective instrument for the government to stimulate green innovation only when they are vital in reducing carbon emissions. Finally, we can summarize the evolutionary process of carbon mitigate from mandatory green fiscal policies to independent green investment, which is helpful for green governance and the low-carbon development of enterprises.